BRAND IMAGE AND PURCHASING DECISION: ANALYSIS OF PRICE PERCEPTION AND PROMOTION (LITERATURE REVIEW OF MARKETING MANAGEMENT) - Hazrati Havidz, Hazimi Bimaruci; Mahaputra, M. Rizky (Dinasti Publisher, 2020)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. This article reviews the factors that influence brand image and purchasing decision, namely: price perception and promotion, a Marketing Management Literature Study. The results of this research library are that: 1) Price perception has a relationship and affects the brand image; 2) Price perception has a relationship and affects purchasing decision; 3) Promotion has a relationship and affects the brand image. 4) Promotion has a relationship and affects purchasing decisions; and 5) Brand Image has a relationship and affects purchasing decisions.